Ultrafast carrier dynamics in BiVO4 thin film photoanode material: interplay between free carriers, trapped carriers and low-frequency lattice vibrations. Issue 47 (17th November 2016) - Butler, K. T.; Dringoli, B. J.; Zhou, L.; Rao, P. M.; Walsh, A.; Titova, L. V.
Abstract : We explore ultrafast carrier dynamics and interactions of photoexcited carriers with lattice vibrational modes in BiVO4 using time-resolved terahertz spectroscopy and first-principles phonon spectrum calculations. Abstract : We explore ultrafast carrier dynamics and interactions of photoexcited carriers with lattice vibrational modes in BiVO4 photoanode material using time-resolved terahertz spectroscopy and first-principles phonon spectrum calculations. We find that photoexcited holes form bound polaron states by introducing lattice distortion that changes phonon spectrum and suppresses the Ag phonon mode associated with opposite motion of Bi and VO4 molecular units. At excitation fluence higher than 1 mJ cm −2 (or 2 × 10 15 cm −2 per pulse), lattice distortion due to self-localized holes alters the lattice symmetry and vibrational spectrum, resulting in bleaching of THz absorption by Ag phonons. Concurrently, we observe a short lived population of free carriers which exhibit Drude conductivity with mobility on the order of 200 cm 2 V −1 s −1, orders of magnitude higher than typical carrier mobility in BiVO4 . The anomalously high carrier mobilities are explained in the framework of a Mott transition. This demonstration of enhanced transport suggests how engineering BiVO4 photoanodes to take advantage of free carrier transport under high excitation conditions may in the future significantly enhance performance of photoelectrochemical devices.